2002
DOI: 10.1097/00004691-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Motor Unit Number Estimates in Juvenile Myoclonic Epilepsy

Abstract: In this study, motor unit number estimate (MUNE) analysis with McComa's technique was used to detect any change in lower motor neuron count in juvenile myoclonic epilepsy (JME). The study included 10 JME patients, 8 idiopathic generalized epilepsy (IGE) patients, 7 patients with mesial temporal sclerosis (MTS), and 15 normal subjects. All the patients and normal subjects were subjected to MUNE analysis on the abductor pollicis brevis and tibialis anterior muscles, as well as needle electromyography and nerve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The incremental method assumes each increment in CMAP waveform size (as stimulus intensity is progressively increased during a standard motor NCS) corresponds to the addition of another single motor unit to the growing CMAP waveform and further assumes that an average SMUP size can be calculated by dividing the size of the maximal CMAP by the average size of its stepwise increases (usually numbering 8–10 or more) . Incremental stimulation was the original MUNE method and is the most widely reported to date, producing over 50 articles through 2010, more than any other method.…”
Section: Mune Methodsmentioning
confidence: 99%
“…The incremental method assumes each increment in CMAP waveform size (as stimulus intensity is progressively increased during a standard motor NCS) corresponds to the addition of another single motor unit to the growing CMAP waveform and further assumes that an average SMUP size can be calculated by dividing the size of the maximal CMAP by the average size of its stepwise increases (usually numbering 8–10 or more) . Incremental stimulation was the original MUNE method and is the most widely reported to date, producing over 50 articles through 2010, more than any other method.…”
Section: Mune Methodsmentioning
confidence: 99%
“…1416 Recently, disorganization of lower motor neurons in a small group of JME patients has been shown by MUNE analysis, like in our group's large-scale study. 17 MUNE analysis is a quantitative electrophysiological method used to measure the loss of lower motor neurons in neurogenic diseases. 19 Modified McComas' method estimates the number of motor units in a target muscle by dividing the area of compound muscle action potential by the average area of single motor unit potential.…”
Section: Discussionmentioning
confidence: 99%
“…1416 Recently, motor unit number estimation (MUNE) analysis was used to count the functioning lower motor neurons in a small JME series, and it was reported that the number of lower motor neurons in spinal cord were nearly half of those of the normal controls. 17…”
Section: Introductionmentioning
confidence: 99%
“…Large macro MUAPs with slightly increased fiber density (FD) found with macro EMG and decreased number of motor units found with the motor unit number estimate (MUNE) method suggested the preponderance of normal large motor units [9].…”
Section: Introductionmentioning
confidence: 99%
“…Above techniques provide only an estimate to MU size and do not give an insight about MU unit territory [9]. Therefore, a scanning EMG technique that reflects spatial and temporal characteristics of the MU is considered to reveal the preponderance of large MUs.…”
Section: Introductionmentioning
confidence: 99%